2011
DOI: 10.1111/j.1365-2559.2010.03706.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of the microenvironment in B-cell lymphomas

Abstract: B-cell non-Hodgkin lymphomas (B-NHL) represent the most common malignant lymphoid neoplasms, with the majority of these arising from germinal centre or post-germinal centre B cells, due to (at least) a disruption of the different phases of normal B-cell development. The most common B-cell lymphoma subtypes include follicular lymphoma, diffuse large B-cell lymphoma, marginal zone lymphoma and mantle cell lymphoma. As with other malignancies, it has been demonstrated that the development and progression of B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 92 publications
1
34
0
2
Order By: Relevance
“…[45][46][47] In the present study, we found higher miR-155 levels in the stromal cells of patients with WM compared with those from healthy subjects ( Figure 4A). Interestingly, loss of miR-155 in the stroma led to significant inhibition of tumor growth, indicating that miR-155 regulates tumor proliferation not only when it is overexpressed in the malignant cells, but also when it is present in BM microenvironmental cells (Figure 4).…”
supporting
confidence: 50%
“…[45][46][47] In the present study, we found higher miR-155 levels in the stromal cells of patients with WM compared with those from healthy subjects ( Figure 4A). Interestingly, loss of miR-155 in the stroma led to significant inhibition of tumor growth, indicating that miR-155 regulates tumor proliferation not only when it is overexpressed in the malignant cells, but also when it is present in BM microenvironmental cells (Figure 4).…”
supporting
confidence: 50%
“…MLs are malignant neoplasms composed of monoclonal proliferations of lymphocytes derived from either B cells or T cells at various stages of their differentiation [10]. The molecular characteristics and biologic behavior of these tumors differ according to the histologic subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting tumor growth depends on the balance between the inhibitory and growth-promoting signals [176,177]. Thus, in each tissue, lymphoma cells presents an unique network of signals, and therefore is hard to get targeted therapies [175,178].…”
Section: Lymphoma Microenvironmentsmentioning
confidence: 99%